Walks4Work: Assessing the role of the natural environment in a workplace physical activity intervention - Daniel K Brown; Jo L Barton; Jules Pretty; Valerie F Gladwell (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: The primary aim of this study was to examine the impact of physical activity (PA) in the natural environment (eg, "green exercise") on resting autonomic function in the Walks4Work intervention. A secondary aim was to assess the feasibility of Walks4Work in terms of adherence, change in PA levels, and cardiovascular health parameters. METHODS: In an 8-week randomized control trial, 94 office workers in an international company were allocated to one of three groups: control, nature (NW), or built (BW) lunchtime walking route. Both walking groups were required to undertake two lunchtime walks each week. The NW route centered around trees, maintained grass, and public footpaths. In contrast, the BW consisted of pavement routes through housing estates and industrial areas. Data were collected at baseline and following the intervention. To investigate the impact of the intervention, mixed-design analysis of variance (ANOVA) were performed. RESULTS: A total of 73 participants completed the intervention (drop-out rate of 22%). No difference was observed in resting autonomic function between the groups. Self-reported mental health improved for the NW group only. PA levels increased at the intervention mid-point for all groups combined but adherence to the intervention was low with rates of 42% and 43% within the BW and NW groups, respectively. CONCLUSION: Accompanying a guideline of two active lunchtimes per week with low facilitator input appears inadequate for increasing the number of active lunchtimes and modifying cardiovascular health parameters in an office population. However, this population fell within normal ranges for cardiovascular measures and future research should consider investigating at-risk populations, particularly hypertensive individuals.